Evaluation of Immune Responses to Tdap Booster During Pregnancy in Women Who Received Whole Cell or Acellular Pertussis Vaccines During Childhood - Jesse M. Hall; Kyle J. Caution; Kia J.A. Holt; Yash A. Gupta; Myra Guo; Umul Q. Mir; Tami H. Skoff; Susan Hariri; Xueliang Pan; Brett Worly; Purnima Dubey (Emerging Microbes and Infections)
Pertussis, caused by Bordetella pertussis (Bp), results in severe morbidity and mortality in infants. Since 2012, the tetanus, diphtheria and pertussis (Tdap) booster vaccine is recommended during every pregnancy to protect infants who are too young to be immunized. While infants of whole cell pertussis vaccine (wPV)-primed pregnant individuals are well protected from severe disease, the effectiveness of this strategy has not been assessed in acellular pertussis vaccine (aPV)-primed pregnant women. Our primary objective was to compare the cellular and humoral immune responses following Tdap booster in pregnant participants who received the wPV or aPV as infants. As a secondary objective we compared responses of pregnant women to wPV- and aPV-primed non-pregnant controls. All pertussis and non-pertussis specific serum antibody levels increased post-Tdap booster in aPV- and wPV-primed groups. Antibody avidity was higher in wPV-primed pregnant participants compared to aPV-primed pregnant women before and after Tdap booster. In contrast, antibody opsonic activity remained unchanged in either priming group. Antibody secreting cells specific for all pertussis and non-pertussis antigens increased following booster immunization. Expression of early T cell activation markers OX-40, PD-L1 and CD25 and cytokines IFNγ, IL-17 and IL-4 showed that T cell function was unaffected by Tdap booster and maintained the phenotypes elicited by the childhood priming vaccine. Secondary analysis showed that antibody and T cell responses to Tdap booster were higher in nonpregnant control participants compared to pregnant women, suggesting that responses to Tdap booster were blunted in pregnancy.